Bar Yarns and Manic-Depressive Mixtapes : Jim Walsh on Music from Minneapolis to the Outer Limits - Walsh, Jim, 1959- (Book collections on Project MUSE., 2016)
Bar Yarns and Manic Depressive Mix Tapes" distills thirty delirious, jam-packed years of some of the best music writing ever to come out of the Twin Cities. As a writer and musician, the ever-curious Jim Walsh has lived a life immersed in music, and it all makes its way into his columns and feature articles, interviews and reviews, including personal essays on life, love, music, family, death, and, yes, the manic-depressive highs and lows that come with being an obsessive music lover and listener. From Minneapolis?s own Prince to such far-flung acts as David Bowie, the Waterboys, Lucinda Williams, Parliament-Funkadelic, L7, the Rolling Stones, the Ramones, U2, Hank Williams, Britney Spears, Elvis Presley and Nirvana, Walsh?s work treats us to a chorus of the voices and sounds that have made the music scene over the past three decades. The big names are here, from Rosanne Cash to Bruce Springsteen to Bob Marley and Jackson Browne, but so are those a little shy of superstardom, like the Tin Star Sisters and Uncle Tupelo, Son Volt, the Gear Daddies, Semisonic, and The Belfast Cowboys.